Up to the Challenge: Adapting Pediatric Intensive Care During a Global Pandemic - Myra Pereira; Olugbenga Akinkugbe; Laura Buckley; Laura Buckley; Laura Buckley; Elaine Gilfoyle; Elaine Gilfoyle; Elaine Gilfoyle; Sarah Ibrahim; Sarah Ibrahim; Sarah Ibrahim; Melissa McCradden; et al. (Frontiers in Pediatrics, 2022)
BackgroundThe COVID-19 pandemic has strained health systems world wide. In our region, surging numbers of critically ill adult patients demanded urgent system-wide responses. During the peak of the pandemic, our Pediatric Intensive Care Unit (PICU) team redesigned the existing educational resources and processes of care to ensure for adult patients for the first time in the hospital’s history.AimDescribe the experiences and impacts of the rapidly initiated Adult COVID-19 Program on health care providers (HCP) and family members. Havelock’s Theory of Change framed the examination of Adult COVID-19 Program participant experiences and surfaced lessons learned.Materials and MethodsA quality improvement review was employed to collect feedback about the program experience from the health care team and patient’s family members. HCP completed a questionnaire 10 months following the implementation of the program and feedback from family members was provided during the program was obtained. Havelock’s Theory of Change was used to explore trends and frame participants’ experiences.ResultsPediatric Intensive Care Unit bedside team members and clinical leaders (n = 17), adult hospital partners (n = 3), and family members (n = 8) participated. HCP describe; motivation and readiness; concern for personal safety and uncertainty experienced in the early program phases; the importance of supports and resources; use of relationships and collaboration to facilitate change; the emotional impacts of this unique experience; and opportunities for individual and team growth. An overarching theme of ‘doing our part to help’ emerged. Family members described the positive impacts of family-centered interventions offered, individualized care, and shock at their family member’s illness.ConclusionThe PICU team rapidly adapted to provide care for adults at the peak of the pandemic. Family members expressed feeling grateful for the care their loved ones received in the pediatric setting. The experience of caring for adult patients with COVID-19 was a source of tension, personal growth, and meaning for the pediatric intensive care team.